Dyslipidemia among patients with type 2 diabetes in Jordan: Prevalence, pattern, and associated factors - Hyassat, Dana; Al-Saeksaek, Saba; Naji, Duha; Mahasneh, Awn; Khader, Yousef; Abujbara, Mousa; El-Khateeb, Mohammad; Ajlouni, Kamel (Frontiers in Public Health, 2022)
Objectives To determine the prevalence and patterns of dyslipidemia and its associated risk factors among patients with type 2 diabetes attending the National Center for Diabetes, Endocrinology, and Genetics (NCDEG). Methods A cross-sectional study was conducted at the NCDEG in Amman, Jordan. A total of 971 patients with type 2 diabetes were included during the period September- December 2021. The socio-demographic data were collected through face-to-face interview questionnaire and anthropometric and clinical data were abstracted from medical records. The last three readings of lipid profile and HbA1C were abstracted from the medical records. Results The overall prevalence of dyslipidemia among type 2 diabetic patients was 95.4%. The most common type of dyslipidemia was combined dyslipidemia (37.1%), with high triglycerides and low HDL-c (19.0%) being the most frequent type. Factors associated with hypercholesterolemia were diabetes duration ≤ 10 years, poor compliance to a statin, and HbA1c level (7–8%) (P-values: 0.008, 0.001, 0.021, respectively). Moreover, smoking and poor compliance with statin therapy were associated with high LDL-c level (P-values: 0.046 and 0.001, respectively). The presence of hypertension, high waist circumference, HbA1c level >8%, and diabetes duration ≤ 10 years were all associated with high triglyceride level (P-values: 0.008, 0.016, 0.011, and 0.018, respectively). Hypertension and HbA1c level >8% were associated with low HDL-c level (P-values: 0.010 and 0.011, respectively). Conclusion The combination of high triglyceride and low HDL-c is the commonest lipid abnormality detected in patients with type 2 diabetes. An educational program that emphasizes the importance of adherence to a healthy lifestyle is strongly recommended. Further studies are needed to capture a wide range of factors that might influence dyslipidemia and glycemic control.